Deliberating the Constitutional Supremacy from Legal Perspective in Palestine - Hamad, Ahmed M.A; Anuar, Haslinda binti Mohd. (Yustisia, 2022)
The system of government considers constitutional supremacy in which the freedom of the legislature of parliamentary supremacy relinquishes to the requirements of a constitution. This article examines the constitutional supremacy of basic law from the legal and judicial perspective, particularly concerning the Palestinian situation. In addition, constitutions differentiate according to whether they are codified or not into written constitutions and unwritten constitutions. Besides, constitutions differ in how they are amended into flexible and rigid constitutions. Palestinian Basic Law of 2003 is not explicitly provided with any legal provision or article in the Basic Law about the principle of constitutional supremacy or the supremacy of the basic law. However, some elements and legal provisions or articles could make the Basic Law supreme. The article aims to clarify the decline of the concept of constitutional supremacy or the supremacy of the basic law from the legal and judicial perspective, with particular reference to the Palestinian situation. Moreover, constitutional oversight secured the supremacy of the Basic Law of 2003. These main findings show that the Palestinian Basic Law of 2003 has adopted the principle of supremacy of the Basic Law of 2003 over ordinary laws and subsidiaries within the state of Palestine. The article also emphasises the need to explicitly mention the principle of constitutional supremacy or the supremacy of the basic law by amending the Basic Law of 2003